2009
DOI: 10.1007/s00259-008-1057-x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter binding with [123I]β-CIT SPECT in major depressive disorder versus controls: effect of season and gender

Abstract: Purpose The serotonin system is undoubtedly involved in the pathogenesis of major depressive disorder (MDD). More specifically the serotonin transporter (SERT) serves as a major target for antidepressant drugs. There are conflicting results about SERT availability in depressed patients versus healthy controls. We aimed to measure SERT availability and study the effects of age, gender and season of scanning in MDD patients in comparison to healthy controls. Methods We included 49 depressed outpatients (mean±SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 44 publications
5
38
3
Order By: Relevance
“…Using [ 11 C]DASB and PET, we were able to show that serotonin transporter binding varies across seasons, with highest binding measured in fall and winter, and lower binding measured in spring and summer, with peak differences being as high as 40% (Praschak-Rieder et al, 2008). A seasonal variation in brain serotonin transporter binding has also been found with [ 11 C]McN 5652 and PET (Buchert et al, 2006), and with [ 123 I]β-CIT and SPECT (Ruhe et al, 2009), as well as in another recent study using [ 11 C]DASB and PET (Kalbitzer et al, 2010). These studies unanimously show that serotonin transporter binding is higher in fall and winter as compared to spring and summer.…”
Section: Serotonin Transporter Gene Linked Polymorphic Region (5-httlpr)supporting
confidence: 66%
“…Using [ 11 C]DASB and PET, we were able to show that serotonin transporter binding varies across seasons, with highest binding measured in fall and winter, and lower binding measured in spring and summer, with peak differences being as high as 40% (Praschak-Rieder et al, 2008). A seasonal variation in brain serotonin transporter binding has also been found with [ 11 C]McN 5652 and PET (Buchert et al, 2006), and with [ 123 I]β-CIT and SPECT (Ruhe et al, 2009), as well as in another recent study using [ 11 C]DASB and PET (Kalbitzer et al, 2010). These studies unanimously show that serotonin transporter binding is higher in fall and winter as compared to spring and summer.…”
Section: Serotonin Transporter Gene Linked Polymorphic Region (5-httlpr)supporting
confidence: 66%
“…Furthermore, SERT availability might be confounded by factors such as gender (Staley et al, 2001) and smoking habits (although less than one third of our patients reported smoking). We saw no effect of season on baseline SERT availability in our cohort, whereas such an influence was recently reported in an earlier study in a large patient group (Ruhe et al, 2009a).…”
Section: Discussioncontrasting
confidence: 51%
“…We performed measurements on healthy subjects. Because several medical conditions can influence brain SERT (e.g., Parkinson disease and Lewy bodies dementia (5,6), panic disorder (19), and depression (22,23)), it is unknown at present whether peak extrastriatal SERT binding of 123 I-FP-CIT is similar in subjects with any of these diseases. This topic also needs further investigation.…”
Section: Discussionmentioning
confidence: 99%